Filosofia e vida : os dois sentidos de compreensão da realidade – Henri Bergson - Aruan Fernandes Gonçalves (2022)
The objective of this work is to follow the movement of Bergsonian philosophy through the search for a more intimate knowledge of reality is articulated with the study of life. First, applied to the environment of inner life and the work Time and Free Will, we seek to demonstrate how the philosopher finds that the sense of knowledge usually applied to external material realities, invariably errs when trying to transcribe the inner consciousness, temporal and psychological, in the same way as extensive spatial realities. Subsequently, applied to the work Creative Evolution, we contemplate Bergson's biological discussions, which contribute to demonstrate that beyond the sense of knowledge of inert, static and mechanically articulated realities, life itself incites the consideration of a continuous real, dynamic and progressive, which is better understood from the perspective of duration. Thus, we intend to demonstrate the ways in which Bergson's major consideration of the Vida instance opens the horizons of Western thought for a philosophy attentive to time, movement and the real.